Monocyte Tissue Factor Expression: Lipopolysaccharide Induction and Roles in Pathological Activation of Coagulation - Sachetto, Ana T. A.; Mackman, Nigel (Thrombosis and Haemostasis, 2023)
The coagulation system is a part of the mammalian host defense system. Pathogens and pathogen components, such as bacterial lipopolysaccharide (LPS), induce tissue factor (TF) expression in circulating monocytes that then activates the coagulation protease cascade. Formation of a clot limits dissemination of pathogens, enhances the recruitment of immune cells, and facilitates killing of pathogens. However, excessive activation of coagulation can lead to thrombosis. Here, we review studies on the mechanism of LPS induction of TF expression in monocytes and its contribution to thrombosis and disseminated intravascular coagulation. Binding of LPS to Toll-like receptor 4 on monocytes induces a transient expression of TF that involves activation of intracellular signaling pathways and binding of various transcription factors, such as c-rel/p65 and c-Fos/c-Jun, to the TF promoter. Inhibition of TF in endotoxemia and sepsis models reduces activation of coagulation and improves survival. Studies with endotoxemic mice showed that hematopoietic cells and myeloid cells play major roles in the activation of coagulation. Monocyte TF expression is also increased after surgery. Activated monocytes release TF-positive extracellular vesicles (EVs) and levels of circulating TF-positive EVs are increased in endotoxemic mice and in patients with sepsis. More recently, it was shown that inflammasomes contribute to the induction of TF expression and activation of coagulation in endotoxemic mice. Taken together, these studies indicate that monocyte TF plays a major role in activation of coagulation. Selective inhibition of monocyte TF expression may reduce pathologic activation of coagulation in sepsis and other diseases without affecting hemostasis.
Keywords: coagulation; inflammation; lipopolysaccharide; monocytes; tissue factor